Family functioning in paediatric obsessive compulsive and related disorders. (28th May 2015) - Murphy, Yolanda E.; Flessner, Christopher A.
<x xml:space="preserve">Abstract</x> Objective Research among youths with obsessive compulsive disorder (OCD) has shown a significant relationship between illness severity, treatment outcome, and the family environment yet little work has been undertaken among the broader class of obsessive compulsive and related disorders (OCRDs) – Trichotillomania, body dysmorphic disorder (BDD), skin picking disorder (SPD), and hoarding. The aim of this study was to (1) review the family functioning literature among paediatric OCRDs, (2) address limitations to previous studies, and (3) highlight areas in need of further research. Methods A review of the literature was conducted using several databases (i.e., Google Scholar, PubMed, ScienceDirect) and employing key search terms (e.g., 'family functioning', 'paediatric OCD'). The resultant articles examined several domains subsumed under the broader heading of family environment including parental mental health, parenting practices, family dynamics, family involvement with symptoms, and family emotional climate. Results The literature reviewed demonstrated a strong relationship between paediatric OCD and adverse family functioning (e.g., parental symptoms of anxiety and depression, family accommodation, family strain and stress, parental guilt and fear) in all identified domains. While family functioning research in paediatric HPD was relatively scant, research suggested similar familial dysfunction (e.g., limited independence, low family cohesion, family violence). Collectively, only 1 article, examining BDD, assessed family functioning within other OCRDs. Conclusions This review supports the need for further research in the OCRDs. Limitations to the available literature and targeted suggestions for future research are discussed. Practitioner points The domains of family environment in this study indicate specific family functioning deficits that may serve as aetiological and/or maintenance factors in paediatric OCRDs, possibly contributing to the understanding of these complex disorders. The recognition of family deficits in paediatric OCRDs may prove beneficial in developing or bolstering preventative and/or therapeutic interventions. Insufficient number of articles pertaining to family functioning in some paediatric OCRDs (i.e., hoarding, skin picking) inhibits formal conclusions. Magnitudes of family functioning effects were not calculated; therefore, future research should consider meta‐analytic analyses.